Assessment of Job Satisfaction of Civil Engineers Working in the Transportation Sector of Bagmati Province, Nepal - Musyaju, Samir; Sukamani, Dinesh; Kusi, Manita (Journal of Engineering and Technological Sciences, 2025)
This is a quantitative study approach that aims to assess the job satisfaction among civil engineers employed in the Transportation Sector of Bagmati Province, Nepal. The Minnesota Satisfaction Questionnaire was used for the survey, and different analytical methods were used to look at the data. These included Principal Component Analysis (PCA), Structural Equation Modelling (SEM), and the Maximum Degree of Membership (MDM) principle for data analysis. The study found significantly low job satisfaction levels among transportation sector civil engineers. Four critical factors were identified as directly affecting job performance (JP): work culture (WC), work-life balance (WLB), employee engagement (EE), and job security (JSE). Notably, work culture emerged as the most influential component, accounting for 43.101% of the total variance (Eigenvalue = 10.344) in job satisfaction levels. These findings highlight WC as the predominant factor shaping engineers' performance and satisfaction in the sector. Moreover, SEM approach analysis confirmed the direct and significant relationship between work culture, work-life balance, employee engagement, and job performance. Meanwhile, there is a poor level of job satisfaction among private-sector civil engineers compared to government civil engineers. This research offers valuable insights regarding the determinants of job satisfaction among civil engineers in transportation and recommends strategies to improve their performance and enhance employee retention